Orlando Fals Borda: la corriente romántica de la sociología en América Latina, 1959-1989 - Pereira Fernández, Alexander (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The intention of this thesis is to provide an approach to the life and the Colombian sociologist's work Orlando Fals it Embroiders (1925 -2008). What the reader has among hands consists on a series of writings that you/they go guided to explore the most outstanding edges in this author's thought, inside what can be considered an intellectual biography. From that biographical focus, we seek to demonstrate that the ideological perspective that succeeded in maturing Orlando Fals Embroiders it is a variant peculiar of certain current of romanticism anticapitalista that is possible to find in its works, as manifestation peculiar of the intellectual radicalización that took place among diverse scientific social of Colombia and Latin America in the years sixty and eighty. Understanding the romanticism anticapitalista like a protest that it possesses a perspective of moral strong base that expresses a quarrel against the desarrollismo and the modernization industrial capitalist. The above-mentioned is, in rigor, our central hypothesis of work.

La intención de esta tesis es proporcionar un acercamiento a la vida y obra del sociólogo colombiano Orlando Fals Borda (1925-2008). Lo que el lector tiene entre manos consiste en una serie de escritos que van encaminados a explorar las aristas más relevantes del pensamiento de este autor, dentro de lo que puede considerarse una biografía intelectual. Desde ese enfoque biográfico, pretendemos demostrar que la perspectiva ideológica que alcanzó a madurar Orlando Fals Borda es una variante particular de cierta corriente de romanticismo anticapitalista que es posible encontrar en sus obras, como manifestación particular de la radicalización intelectual que tuvo lugar entre diversos científicos sociales de Colombia y América Latina en los años sesenta y ochenta. Entendiendo el romanticismo anticapitalista como una protesta que posee una perspectiva de base moral fuerte, que expresa una querella contra el desarrollismo y la modernización industrial capitalista. Lo anterior es, en rigor, nuestra hipótesis central de trabajo.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2009-0003; Opción en historia de América; Corriente romántica; Sociología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2388